NounBank.DS: a Lexical Repository of Nominal Frames from Stock Market Tweets in Brazilian Portuguese - Barbosa, Bryan K. S.; Di Felippo, Ariani (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2025)
This paper describes NounBank.DS, a project that provides argument structure for instances of predicate nouns in DANTEStocks, a Dependency-Analyzed corpus of stock market Tweets in Portuguese. NounBank.DS is part of a larger effort to add additional semantic layers of annotation to DANTEStocks. This and other annotation projects taken together should lead to the creation of better tools for the automatic analysis of tweets on the stock market. This paper describes the NounBank.DS project in detail, including its specifications and the process involved in creating the resource.